Specific detection of Trichophyton rubrum and Trichophyton interdigitale based on loop‐mediated isothermal amplification (LAMP) from onychomycosis specimens. Issue 12 (20th September 2019) - Watanabe, Shinichi; Okubo, Akihiro; Miyajima, Yoshiharu; Satoh, Kazuo; Makimura, Koichi
Abstract: In diagnosing onychomycosis, diseases with similar features must be excluded by demonstrating the presence of fungal infection and identifying the fungal species. However, fungal culture of onychomycosis‐derived samples usually takes many weeks to yield species identification results, and is associated with a low successful culture rate. Loop‐mediated isothermal amplification (LAMP) is a highly sensitive and specific molecular biological method that can amplify DNA at a constant temperature, allowing for a simpler testing procedure, shorter detection time and less cost than conventional techniques including quantitative polymerase chain reaction. We have developed a new LAMP method specifically to detect Trichophyton rubrum ( T. rubrum ) and Trichophyton interdigitale ( T. interdigitale ), major causative dermatophytes for onychomycosis, and analyzed the correlation between LAMP results and those of the existing fungal culture method for the detection and identification of Trichophyton species from onychomycosis‐derived samples. The results showed that all 59 specimens in which T. rubrum or T. interdigitale was identified by fungal culture also tested positive by LAMP, giving a 100% positivity concordance rate between the two methods. Moreover, all 55 and four specimens in which T. rubrum and T. interdigitale were identified by fungal culture, respectively, also tested positive for each species by LAMP, again giving a 100% species‐identification concordance rate. The high correlation demonstrated between LAMP and fungal culture results in detection and identification of Trichophyton species from onychomycosis‐derived samples suggests high reliability of LAMP as a promising, alternative mycological detection and identification technique which can serve as an alternative to the fungal culture method.